Engineering materials. 1 : an introduction to properties, applications and design - Ashby, M. F.; Jones, David R. H. 1945- (Butterworth-Heinemann, 2018)
This text gives a broad introduction to the properties of materials used in engineering applications, and is intended to provide a course in engineering materials for students with no previous background in the subject. Widely adopted around the world, Engineering Materials 1 is a core materials science and engineering text for third- and fourth-year undergraduate students; it provides a broad introduction to the mechanical and environmental properties of materials used in a wide range of engineering applications. The text is deliberately concise, with each chapter designed to cover the content of one lecture. As in previous editions, chapters are arranged in groups dealing with particular classes of properties, each group covering property definitions, measurement, underlying principles, and materials selection techniques. Every group concludes with a chapter of case studies that demonstrate practical engineering problems involving materials. The 5th edition boasts expanded properties coverage, new case studies, more exercises and examples, and all-around improved pedagogy. Engineering Materials 1, Fifth Edition is perfect as a stand-alone text for a one-semester course in engineering materials or a first text with its companion Engineering Materials 2: An Introduction to Microstructures and Processing, in a two-semester course or sequence.
Previous edition: 2012.
Keywords: Materials.; elektronické knihy; electronic books